2015
DOI: 10.1038/gim.2014.106
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X full mutation expansions are inhibited by one or more AGG interruptions in premutation carriers

Abstract: AGGs. Two contractions in maternal transmission were accompanied by loss of AGGs, suggesting a mechanism for generating alleles that lack AGG interruptions. Maternal age was examined as a factor in full mutation expansions using prenatal samples to minimize ascertainment bias, and a possible effect was observed though it was not statistically significant (P = 0.06). Conclusion:These results strengthen the association of AGG repeats with CGG repeat stability and provide more accurate risk estimates of full muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 26 publications
6
131
0
1
Order By: Relevance
“…A subsequent study also confirmed the association between PM allele length and FM expansion risk [61]. Unstable allelic transmissions are also related to the lower density of repeat-stabilizing AGG anchors located at the 5′ end of the FMR1 CGG-repeat region [62,63,64,65,66]. Uninterrupted CGG tracts are thought to mediate allelic instability via the formation of stable, hair-pin structures that promote strand slippage during replication.…”
Section: Repeat Instability Of Pm-sized Allelesmentioning
confidence: 91%
“…A subsequent study also confirmed the association between PM allele length and FM expansion risk [61]. Unstable allelic transmissions are also related to the lower density of repeat-stabilizing AGG anchors located at the 5′ end of the FMR1 CGG-repeat region [62,63,64,65,66]. Uninterrupted CGG tracts are thought to mediate allelic instability via the formation of stable, hair-pin structures that promote strand slippage during replication.…”
Section: Repeat Instability Of Pm-sized Allelesmentioning
confidence: 91%
“…Recent studies propose that genetic and environmental factors may influence the process of expansions differently from those leading to repeat contractions [24,39], though their outcomes show the same underlying process. The bulk of evidence suggests that expansion can occur during transcription or open chromatin configuration involving DNA repair independently from genomic replication.…”
Section: Discussionmentioning
confidence: 99%
“…A man with a premutation or full mutation allele passes on a premutation allele to all his daughters and the increase in size is generally small [24]. Cases of contractions of maternal premutation alleles have been reported, but are rare [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the risk of FXTAS and FXPOI, female PM carriers are also at risk of transmitting a FM allele to their children. This risk is directly related to the number of maternal CGG-repeats but is reduced by the presence of one or more AGG interruptions in the repeat tract (Eichler et al 1994; Latham et al 2014; Nolin et al 2015; Nolin et al 2013; Yrigollen et al 2012; Yrigollen et al 2014). In contrast to PM alleles, most FM alleles are epigenetically silenced (Coffee et al 2002; Coffee et al 1999; Kumari and Usdin 2010; Oberle et al 1991; Pieretti et al 1991; Sutcliffe et al 1992), and thus make little of the FMR1 gene product, FMRP, a protein important for learning and memory.…”
Section: Introductionmentioning
confidence: 99%